"Alquimagia Circus Show": a show of integration between Chemistry and circus (Research, Society and Development, 2020)
This work includes an experience report of the event "Alchemia Circus Show" organized by the Chemistry center of IFMG- Campus Bambuí and that involved the association between the discipline of chemistry and the numbers presented in circus shows. The methodology adopted consisted of dividing the students who attended the chemistry disciplines and who belonged to the integrated and higher technical courses, into eight teams. Each of these was responsible for developing a circus presentation, relating chemistry in their numbers in a presentation of 10 to 15 minutes. The presentations took place in the open amphitheater of the Campus, with the presence of the community, as well as that of servers that did not belong to the said chemistry center with their families. The teams were evaluated by a bank composed of internal and external servers to the Campus. The results revealed that the event developed succeeded in that in addition to contemplating chemistry in the circus, it was able to integrate the participants, coordinators, evaluators and visiting public in a true show. The results indicated that the event can act as a didactic-pedagogical resource favoring the teaching and learning process.